An Effective Distributed Space-Time Code for Two-Path Successive Relay Network - Feng Tian; Wei Zhang; Wing-Kin Ma; Ching, P. C.; Poor, H. V. (IEEE transactions on communications, 2011)
Two-path successive relaying has recently been proposed as a mechanism for recovering the multiplexing loss of conventional relay networks; however, the full diversity cannot be guaranteed with this method. In this paper, distributed space-time block coding (STBC) is proposed for a two-path successive decode-and-forward relay network that can achieve both full rate and full diversity when perfect decoding is enabled at the relays. For the case of imperfect decoding, selection relaying is proposed with the distributed STBC to recover the full diversity. For the practical scenario in which the inter-relay channel is subject to fading, the two-path successive relaying transmission may not always be successful; for such cases an adaptive relaying scheme is proposed that can select a proper transmission mode between two-phase relaying transmission and two-path successive relaying transmission based on the channel quality of the relay network. Analytical results show that the proposed distributed STBC can offer both full diversity and a large symbol rate gain.